Tourism film and its influence on destination image and intentions for Indonesian tourist visits to South Korea - Stephanie Hermawan Telim; Gabriella Griseldis; Serli Wijaya (Jurnal Pariwisata Pesona, 2022)
Film tourism is a tourist trip to a destination that is a location in a film or television drama. This study aims to examine the influence of film tourism elements consisting of place, personality, and performance on the destination image and on film tourism visit intention and to determine the effect of destination image in mediating the influence of film tourism elements on film tourism visit intention. The online survey was distributed to 183 respondents who like South Korean films or dramas. This study uses SEM-PLS for primary data processing. The results showed that the three elements of South Korean film tourism had a positive and significant effect on the destination image formation of South Korea among Indonesian tourists. Destination image has a positive and significant effect on Indonesian tourists’ intention to undertake film tourism in South Korea. Destination image has been shown to significantly mediate the influence of film tourism elements on Indonesian tourists’ visit intention to involve in film tourism in South Korea.